2020
DOI: 10.18632/aging.103095
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: the updated protective property in kidney disease

Abstract: With an aging population, the burden of kidney disease gradually occupies more and more medical resources. Between 2013 and 2016, chronic kidney disease (CKD) was reported in 14.8% of the United States (US) general adult population. As of December 31, 2016, there are 2,160.7 patients with end stage renal disease (ESRD) per 1,000,000 US citizens, according to the US Renal Data System's latest Annual Data Report [1]. Therefore, there is an urgent demand for effective drugs to delay kidney impairment.Beyond its h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 132 publications
(146 reference statements)
0
13
0
Order By: Relevance
“…However, its effects are likely pleiotropic because metformin acts on the metabolism and inflammation via both adenosine monophosphate-activated protein kinase (AMPK)-dependent and AMPK-independent mechanisms, leading to kidney protection. Potential uses of metformin in kidney disease have been extensively reviewed elsewhere [ 15 , 16 , 17 ].…”
Section: Metforminmentioning
confidence: 99%
“…However, its effects are likely pleiotropic because metformin acts on the metabolism and inflammation via both adenosine monophosphate-activated protein kinase (AMPK)-dependent and AMPK-independent mechanisms, leading to kidney protection. Potential uses of metformin in kidney disease have been extensively reviewed elsewhere [ 15 , 16 , 17 ].…”
Section: Metforminmentioning
confidence: 99%
“…As in other tissues, also in the kidney metformin acts via both AMPK-dependent and -independent pathways as described in the following paragraphs, in which I will concentrate on the effects of metformin in podocytes. For comprehensive reviews covering the effects of metformin in the kidney beyond podocytes, see the following recent review articles [ 93 , 94 , 95 , 96 , 97 ]. The mechanisms of action of metformin in different tissues are reviewed in [ 98 ].…”
Section: Mechanisms Whereby Metformin Reduces Hyperglycaemiamentioning
confidence: 99%
“…Metformin also ameliorates the senescence of renal tubular cells in culture and in diabetic db/db mice by up-regulating miR-130a-3p and down-regulating STAT3, a target gene of miR-130a-3p involved in the pathogenesis of DKD [ 136 ]. For recent reviews on the beneficial effects of metformin in the kidney at large, the readers are referred to [ 93 , 94 , 95 , 96 , 97 ].…”
Section: Podocyte-protective Mechanisms Of Action Of Metforminmentioning
confidence: 99%
“…Growing evidence has revealed that metformin has antitumour, antiageing, cardiovascular protective, anti-inflammatory and immune regulatory effects though AMP-activated protein kinase (AMPK)-dependent and independent pathways. 9 Metformin also protects against renal inflammation and fibrosis in experimental models. 10–12 A registered clinical trial recently analysed metformin as an SLE treatment.…”
Section: Introductionmentioning
confidence: 99%